Carbon dioxide levels and ventilation in Acromyrmex nests: significance and evolution of architectural innovations in leaf-cutting ants - Martin Bollazzi; Daniela Römer; Flavio Roces (Royal Society Open Science, 2021)
Leaf-cutting ant colonies largely differ in size, yet all consume O2 and produce CO2 in large amounts because of their underground fungus gardens. We have shown that in the Acromyrmex genus, three basic nest morphologies occur, and investigated the effects of architectural innovations on nest ventilation. We recognized (i) serial nests, similar to the ancestral type of the sister genus Trachymyrmex, with chambers excavated along a vertical tunnel connecting to the outside via a single opening, (ii) shallow nests, with one/few chambers extending shallowly with multiple connections to the outside, and (iii) thatched nests, with an above-ground fungus garden covered with plant material. Ventilation in shallow and thatched nests, but not in serial nests, occurred via wind-induced flows and thermal convection. CO2 concentrations were below the values known to affect the respiration of the symbiotic fungus, indicating that shallow and thatched nests are not constrained by harmful CO2 levels. Serial nests may be constrained depending on the soil CO2 levels. We suggest that in Acromyrmex, selective pressures acting on temperature and humidity control led to nesting habits closer to or above the soil surface and to the evolution of architectural innovations that improved gas exchanges.